Keterampilan Teknik Dasar Mahasiswa Program Studi Ilmu Olahraga Pasca Mata Kuliah Sepak Bola - Nusri, Ardi; Khairuddin, Khairuddin; Masrun, Masrun (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
The purpose of this study was to determine the level of basic football technical skills for students of the Sports Science Study Program, Medan State University (Unimed IKOR Study Program) after taking courses during the pandemic. The design used in this research is quantitative descriptive. The research method used is a survey method with test and measurement techniques. The research population was all Unimed 2021 Sports Science Department students. The research sample consisted of 60 students. The sampling technique in this study is total sampling.Based on the data analysis carried out, it was found that the basic football technical skills of the Unimed IKOR Study Program students in 2021 as a whole were included in the good category with a score of 357.85. Furthermore, in more detail, students' passing and receiving skills are in the good category with an average of 78.5, dribbling skills are in the good category with an average of 80.61, heading skills are in the good category with an average of 79.7, and shooting skills in the medium category with an average of 79.66. Keywords: Football, Basic Technical Skills, and Pandemic..